2019
DOI: 10.1111/jonm.12728
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to nurse leadership in an Indonesian hospital setting

Abstract: Background Given the prominent role of nursing within modern health care environments, it is essential that leadership is viewed as a key capability. However, little is known on how leadership evolves amongst the nurses in Indonesia and the barriers that exist to nurses gaining access to leadership roles. Limited attention is given to address the improvement of nurse leadership for the benefit of the nurses in the country. Aim To identify organizational and individual practices and how these contribute to barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…5,6,7 o desenvolvimento da liderança em enfermeiros recém-qualificados,8 fatores relacionados à equipe, aos processos de liderança e ao líder 9 e os desafios e estratégias adotados para o exercício da liderança. 10 Os principais fatores mencionados como barreiras ao desenvolvimento das habilidades de liderança foram: pers- pectivas restritas, 5 questões de gênero, 5,7 barreiras contratuais e profissionais, 5,7 questões hierárquicas e de estrutura organizacional, 5,10 ritmo acelerado e mudanças repentinas no ambiente de trabalho, 6 falta de apoio por parte da instituição 7,8,10 e inexperiência profissional e jovialidade. 8,10 Os estudos também apresentaram caminhos para superar este desafio.…”
Section: Resultsunclassified
“…5,6,7 o desenvolvimento da liderança em enfermeiros recém-qualificados,8 fatores relacionados à equipe, aos processos de liderança e ao líder 9 e os desafios e estratégias adotados para o exercício da liderança. 10 Os principais fatores mencionados como barreiras ao desenvolvimento das habilidades de liderança foram: pers- pectivas restritas, 5 questões de gênero, 5,7 barreiras contratuais e profissionais, 5,7 questões hierárquicas e de estrutura organizacional, 5,10 ritmo acelerado e mudanças repentinas no ambiente de trabalho, 6 falta de apoio por parte da instituição 7,8,10 e inexperiência profissional e jovialidade. 8,10 Os estudos também apresentaram caminhos para superar este desafio.…”
Section: Resultsunclassified
“…Despite the substantial professionalization and development of the nursing workforce and education from the 1980s into the 2000s, with the advent of Bachelor of Nursing, Master of Nursing and doctoral degrees, legacies of this hierarchical system remain. Several studies have noted Indonesian nurses reported still encountering stereotypes of being the doctor's subordinate (Shields & Hartati, 2003), lack autonomy and independence in their practice due to the dominance of medical physicians in hospitals and experience barriers in ability to establish nurse leadership roles (Wardani & Ryan, 2018). Whilst the Nursing Act (No.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the health organization's responsibility to promote and provide means for nurses to act autonomously, through the establishment of roles, responsibilities and behaviors, is clearly emphasized (31)(32)(33)(34)(35)(36)(37) .…”
Section: Discussionmentioning
confidence: 99%